Rehabilitation of athletes' after Achilles tendon surgery - A. Belyakova; A. Sereda; A. Samoylov (National Electronic Information Consortium (NEICON), 2020)
Frequency of Achilles tendon injury increases. The lack of standardized methods of rehabilitation after surgery on the Achilles tendon leads to increased risk of repeated injury of tendon and reduces the possibility of coming round to physical activity. Recovery of function is the main task of rehabilitation programs, especially in athletes. This article sets out the basic principles of remedial actions. It can be used with patients of different levels of physical activity and it can be modified according to the task performed and features of surgical treatment in order to achieve optimal results.